2018
DOI: 10.1007/s10522-018-9782-4
|View full text |Cite
|
Sign up to set email alerts
|

Uropygial gland size: a marker of phenotypic quality that shows no senescence in a long-lived seabird

Abstract: Studies of senescence in the wild have traditionally focused on traits like survival or fecundity. Although efforts to measure other salient phenotypic traits and markers of relevant physiological processes are rapidly increasing, traits related to selfmaintenance remain understudied in the context of aging. Uropygial or preen gland is a holocrine gland, exclusive to birds, directly linked to self-maintenance of the quality of plumage. We measured the size of uropygial glands of common gulls (Larus canus) in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
2
0
1
Order By: Relevance
“…All of these birds were caught between the 14 th and 25 th of May, between 10 am and 7 pm, and released immediately after sampling. To minimise the post manipulation nest abandonment, all birds were caught from nests using spring traps after the tenth day of incubation, as previously described and done in the same colony [36][37][38].…”
Section: (B) Field Data Collectionmentioning
confidence: 99%
“…All of these birds were caught between the 14 th and 25 th of May, between 10 am and 7 pm, and released immediately after sampling. To minimise the post manipulation nest abandonment, all birds were caught from nests using spring traps after the tenth day of incubation, as previously described and done in the same colony [36][37][38].…”
Section: (B) Field Data Collectionmentioning
confidence: 99%
“…Aunque son varios los estudios que han analizado los posibles factores que promueven las variaciones de tamaño de la glándula uropigial (ej. Møller, et al 2010;Pap et al 2010;Vincze et al 2013;Jacob et al 2014;Urvik et al 2018;Møller y Laursen 2019), su conocimiento es aún limitado. Dado que el desarrollo de la glándula uropigial podría tener un alto coste energético (Piault et al 2008;Pap et al 2013;Moreno-Rueda 2015), solo aquellos individuos en óptimas condiciones podrían invertir más recursos en defensas antimicrobianas (ej.…”
Section: Española De Ecología Terrestreunclassified
“…It has been reported that the size of the UG is dynamic (e.g. increasing in size from non-breeding to breeding season (Pap et al, 2010;Vincze et al, 2013), and increasing size with age (Urkiv et al, 2018). Even though these modifications might be due to changes in the indexes of cell proliferation and cell death that lead to tissue restructuring, this dynamism could be facilitated by the presence of elastic fibres.…”
Section: Histochemistry and Lectinhistochemistrymentioning
confidence: 99%